An empirical study of moral reasoning among managers in Singapore - Wimalasiri, Jayantha S. (Journal of business ethics, 1996)
The study reported here sought to examine the ethical orientations of business managers and business students in Singapore. Data were obtained using Defining Issue Test. Analysis of Variance revealed that age, education and religious affiliation had influenced cognitive moral development stages of the respondents. Vocation, gender and ethnicity did not seem to have affected moral judgement of the subjects. Contrary to the general view, both business students and business managers demonstrated the same level of sensitivity to ethical dimensions of decision-making. Implications of the findings and limitations of the study are discussed.